On the other side of the forest - Robert, Nadine (Greystone Kids, 2021)
What's on the other side of the forest? A young rabbit and his father are determined to find out in this modern picture book that feels like a classic, calling to mind the tender work of Beatrix Potter. Some say that wolves, ogres, and giant badgers live in the forest beside Arthur's house. That's why no one ever goes in there, to see what's on the other side. But one day, Arthur's dad has an idea--a magnificent idea! Build a tower to look over the treetops! But a magnificent idea takes a lot of work. Will the villagers join and help them? And when the tower takes shape, what will they see on the other side? This wonderful, heartwarming story by Nadine Robert--with illustrations by Gérard DuBois reminiscent of classic children's books--shares the importance of community and cooperation to achieve a big dream.